Integrative Analysis of miRNA and Inflammatory Gene Expression After Acute Particulate Matter Exposure - Motta, Valeria (Oxford University Press, 2013)
MicroRNAs (miRNAs) are environmentally sensitive inhibitors of gene expression that may mediate the effects of metal-rich particulate matter (PM) and toxic metals on human individuals. Previous environmental miRNA studies have investigated a limited number of candidate miRNAs and have not yet evaluated the functional effects on gene expression. In this study, we wanted to identify PM-sensitive miRNAs using microarray profiling on matched baseline and postexposure RNA from foundry workers with well-characterized exposure to metal-rich PM and to characterize miRNA relations with expression of candidate inflammatory genes. We applied microarray analysis of 847 human miRNAs and real-time PCR analysis of 18 candidate inflammatory genes on matched blood samples collected from foundry workers at baseline and after 3 days of work (postexposure). We identified differentially expressed miRNAs (fold change [FC] > 2 and p < 0.05) and correlated their expression with the inflammatory associated genes. We performed in silico network analysis in MetaCore v6.9 to characterize the biological pathways connecting miRNA-mRNA pairs. Microarray analysis identified four miRNAs that were differentially expressed in postexposure compared with baseline samples, including miR-421 (FC = 2.81, p < 0.001), miR-146a (FC = 2.62, p = 0.007), miR-29a (FC = 2.91, p < 0.001), and let-7g (FC = 2.73, p = 0.019). Using false discovery date adjustment for multiple comparisons, we found 11 miRNA-mRNA correlated pairs involving the 4 differentially expressed miRNAs and candidate inflammatory genes. In silico network analysis with MetaCore database identified biological interactions for all the 11 miRNA-mRNA pairs, which ranged from direct mRNA targeting to complex interactions with multiple intermediates. Acute PM exposure may affect gene regulation through PM-responsive miRNAs that directly or indirectly control inflammatory gene expression.